Synergistic Catalysis of SnO2-CNTs Composite for VO2+/VO2+ and V2+/V3+ Redox Reactions - Feng, Xiaojian; Xue, Jing; Zhang, Tongxue; Zhang, Zixuan; Han, Chao; Dai, Lei; Wang, Ling; He, Zhangxing (Frontiers in Chemistry, 2021)
In this paper, SnO2/carbon nanotubes (SnO2-CNTs) composite as catalyst for vanadium redox flow battery (VRFB) was prepared by sol-gel method. Effects of SnO2-CNTs on electrochemical performance of VO2+/VO2+ and V2+/V3+ redox reactions and VRFB performance were investigated. SnO2-CNTs has better catalytic activity and reaction reversibility than pure SnO2 and pure CNTs. This is due to the synergistic catalysis of SnO2 and CNTs. SnO2 mainly provides the catalytic active sites, while CNTs mainly provides the 3D structure and high electrical conductivity. For cell performance, it is found that SnO2-CNTs cell shows greater discharge capacity as well as energy efficiency. Especially at 150 mA cm-2, discharge capacity of SnO2-CNTs cell is 28.6 mA h higher than that of pristine cell. Energy efficiency of modified cell (70.0%) is 7.2% higher than that of pristine cell (62.8%). This study shows that SnO2-CNTs is an efficient and promising catalyst for VRFB.